Empowerment of the Community Through Traditional Art Training in Padangpanjang - Maryelliwati, Maryelliwati (Bhandar: Harvesting Community Service in Asia, 2024)
This community service activity aims to empower the community of Padangpanjang through training in traditional arts. By understanding the dynamics of their arts and culture, it is hoped that the community can preserve and develop traditional art that forms part of their identity. The methods used in the training include observation, socialization, practice, and evaluation. The results of the activities show an increase in interest and skills among the community members in traditional arts, which is expected to enhance their economy and cultural awareness. This increase is particularly important in the face of globalization that threatens the existence of local arts